Nonthermal plasma for pesticide and microbial elimination on fruits and vegetables: an overview - Khanh Thi Kim Phan (2018)
© 2017 Institute of Food Science and Technology Nonthermal plasma (NTP) is defined in terms of partly ionised gas which overall temperature is quite low because the stored energy is mostly in free electrons. Applications of NTP have been expanded to new areas of food applications such as the microbial inactivation and also the elimination of pesticide and toxic chemical residues in food such as fruits and vegetables while nutritional content and key characteristics are still preserved. Plasma treatment has successfully decreased the concentrations of pe sticides by about 45-71%. In this article, NTP technologies as well as investigations about applying of NTP for removing pesticide residues and improving microbial safety in fresh produce are described. Potential applications of NTP in food processing together with some of their challenges and limitations are also discussed.